Classroom Interaction Analysis of Jigsaw Reading Technique in an English Class - Utami, Cahya Ramadanti; Ridwan, Iwan; Saefullah, Hilmansyah (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
This interaction analyis study aims to find out how the interaction between teacher and students and interaction among students in the jigsaw reading technique. The research was conducted qualitatively using interaction analysis involving an English teacher and 32 junior high school students. Data collection was carried out by observing with video recordings. This study was analyzed based on the category of Foreign Language Interaction (FLINT) System developed by Moscowitz (1971). The results show that the interaction patterns occured between teacher and students in the reading jigsaw technique, are giving direction, praising or encouraging, using ideas of students, asking questions, and giving information. Meanwhile, the interaction between fellow students is applied in inter-group discussions and presentations in front of the class. Thus, this research is expected to be a reference for teachers to consider the types of teacher talk that will be applied in jigsaw reading activities to increase the activity and interest of their students during class interactions